Study on Size Dimorphism in Six Juliform Millipedes - Cooper, Mark (New Visions in Biological Science Vol. 8, 2022)
The objective of the present study was to describe Sexual Size Dimorphism (SSD) in the diplopod genera Bicoxidens, Doratogonus, Harpagophora, Julomorpha, and Orthoporoides which has length, width, and rings as the main components of interspecific variation. Interspecific variation in size observed in B. brincki Schubart, [1] D. annulipes Carl, 1917, H. spirobolina (Karsch, 1881), J. hilaris Attems, 1928, J. panda (Attems, 1928), and O. tabulinus (Attems, 1914) and the data sets were tested for normality. Male lengths differed from female lengths in all except J. hilaris which had different widths. Juliform millipedes appear to have decreased in size over evolutionary time and this study presents an interesting finding showing sexual dimorphism based on length in larger species and sexual dimorphism based on width in the smaller species. The reason for this has to do with the constraints imposed through a cylindrical body form which can be changed more powerfully through reducing width rather than length.